2010
DOI: 10.1186/1744-8069-6-69
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase and 5-alpha Reductase Gene Expression: Modulation by Pain and Morphine Treatment in Male Rats

Abstract: BackgroundThe steroid hormone testosterone has been found to be greatly reduced by opioids in different experimental and clinical conditions. The purpose of this study on male rats was to determine the effects of a single injection of morphine (5 mg/Kg) on persistent pain (formalin test) and the single or combined effects on p450-aromatase and 5-alpha reductase type 1 mRNA expression in the brain, liver and testis. Testosterone was determined in the plasma and in the brain, morphine was assayed in the plasma.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 43 publications
0
32
0
1
Order By: Relevance
“…Neurosteroids can be produced by neurons and glial cells in several structures of the nociceptive system (Do Rego et al, 2009). In line with this, the activity and expression of several neurosteroidogenic enzymes were shown to be up-regulated in various pain models (Patte-Mensah et al, 2004Poisbeau et al, 2005;Meyer et al, 2008;Aloisi et al, 2010). The initiating step of neurosteroidogenesis consists of incorporating cholesterol in mitochondria before converting it into pregnenolone, the common precursor of all 3αNS.…”
Section: Introductionmentioning
confidence: 92%
“…Neurosteroids can be produced by neurons and glial cells in several structures of the nociceptive system (Do Rego et al, 2009). In line with this, the activity and expression of several neurosteroidogenic enzymes were shown to be up-regulated in various pain models (Patte-Mensah et al, 2004Poisbeau et al, 2005;Meyer et al, 2008;Aloisi et al, 2010). The initiating step of neurosteroidogenesis consists of incorporating cholesterol in mitochondria before converting it into pregnenolone, the common precursor of all 3αNS.…”
Section: Introductionmentioning
confidence: 92%
“…Our analysis showed that for opioid users with low testosterone, both TT and FT levels can be significantly increased with the use of TRT over 12 months. This is particularly important considering recent findings that morphine administration increased 5‐alpha reductase mRNA expression in the liver and aromatase mRNA expression in the brain and gonads of male rats [25], suggesting that opioids may lead to lower plasma and brain testosterone levels by increasing testosterone metabolism, as well as by their effects on gonadotropin secretion. Thus, exogenous supplementation of testosterone that increases FT throughout the body may be important in maintaining normal levels of mRNA expression and function for the hypogonadal male opioid user.…”
Section: Discussionmentioning
confidence: 99%
“…This reduction of testosterone secretion is mainly attributed to opioid‐induced suppression of GnRH release from hypothalamus . Additionally, a peripheral mechanism of androgen suppression, opioid causes a demonstrable alteration in the expression of 5‐α‐reductase type 1 and/or P 450 aromatase mRNA in peripheral body tissues, which increases the catabolism of testosterone . In a 12‐week prospective trial, Roberts and colleagues demonstrated HPG suppression with intra‐thecal opioid administration, with reduced sexual activity and significantly diminished mean serum testosterone level in 10 chronic non‐cancer pain male patients .…”
Section: Opioid‐induced Hypogonadismmentioning
confidence: 99%
“…53 Furthermore, murine studies demonstrated that morphine reduces serum testosterone by increasing expression of mRNA of (a) testosterone metabolizing enzyme aromatase which enhances conversion of testosterone into estradiol, and (b) 5-alpha reductase an enzyme facilitate the conversion of testosterone into dihydrotestosterone. 54,55…”
Section: Pathophysiology Of Opioid-induced Hypogonadism (Ohg)mentioning
confidence: 99%